Correlation Of Haemoglobin, Leukocytes, Platelet And Neutrophil-Lymphocyte Ratio To Radiotherapy Response In Stage IIB-IIIB Cervical Cancer Patients - Muthmainnah, Muthmainnah; Pelupessy, Nugraha Utama; Rakhmah, Nur; Zainuddin, Andi Alfian; Arifuddin, Sharvianty; Syahrir, Syahruni (Journal of Neonatal Surgery, 2025)
Background: Cervical cancer is a common gynaecological cancer, with high prevalence especially in advanced stages. Radiotherapy is one of the main therapies, but the response to radiotherapy is influenced by several factors. Some studies suggest that haemoglobin, leucocyte, platelet, and neutrophil lymphocyte ratio (NLR) levels may play a role as prognostic indicators in the effectiveness of radiotherapy in cervical cancer. This study aims to analyse the relationship of haemoglobin, leucocyte, platelet and NLR levels to radiotherapy response in stage IIB-IIIB cervical cancer patients. Methods: Analytical observational study with a retrospective cohort approach involving 50 stage IIB-IIIB cervical cancer patients undergoing radiation therapy. Blood profile measurements and radiotherapy response were taken from medical records before and during radiotherapy. Statistical analysis was performed using Chi-square test and logistic regression to determine the relationship between haematological parameters and radiotherapy response. Results: The Friedman test showed a significant decrease in leukocyte levels during radiotherapy (X²=81.54; p<0.001) and platelet levels (X²=61.50; p<0.001), with a downward trend beginning after the 10th radiation session. However, there were no significant differences between hematological parameters (hemoglobin, leukocytes, platelets, and NLR) and treatment response groups (p>0.05). Log-rank analysis of progression-free survival (PFS) indicated that only leukocyte levels had a significant association. Preradiation leukocyte counts ≥8.85 were associated with a higher risk of disease progression (HR=2.96; 95% CI = 1.26–6.94; p=0.013). Conclusion: Leukocytes serve as a prognostic factor in determining progressive response.